Subterranean Politics and Freud’s Legacy - Buzby, A. author. aut Link
VIII, 209 p.
Keywords: Subterranean Politics and Freud's Legacy seeks to reestablish psychoanalysis as an ally to critical theory's efforts to restore subjectivity and oppose systemic domination in modernity. Given critical theory's ongoing crisis of identity and purpose, this project makes a significant contribution to contemporary political theory.